Organic Sulfinic Acids and Salts in Visible Light-Induced Reactions - Lu, Zheng; Shang, Mingzhou; Lu, Hongjian (Synthesis, 2021)
Sulfinic acids and their salts are a useful source of sulfur-containing structures. Photocatalysis of these compounds with visible light enables to achieve various transformations under mild conditions. This review summarizes visible-light-induced reactions of sulfinic acids and their salts. It is organized by reaction type and brief discussions on plausible reaction mechanisms for typical transformations are presented.1 Introduction2 Sulfonylation Reactions2.1 Sulfonylation of Alkenes2.2 Sulfonylation of Alkynes2.3 Sulfonylation of Arenes2.4 sp3 C–H Functionalization3 Desulfonylation Reactions4 Sulfenylation Reactions4.1 Sulfenylation of Heteroarenes4.2 Sulfenylation of Carbonyl Chlorides5 Conclusions
Keywords: sulfinic acid; sulfinate; sulfonylation; cascade reactions; multicomponent; couplings; C–H activation; sulfur